Engineering ethics real world case studies - Starrett, Steve 1967-; Lara, Amy L.; Bertha, Carlos (Reston, Virginia ASCE Press, 2017)
"How do you handle conflicts of interest? Have you ever been offered a kickback or asked for a "voluntary" contribution to a cause? Are there cases where we can - and should - act against an important principle to achieve an even-more-important benefit? To tweet or not to tweet? Entrusted by the public to provide professional solutions to complex situations, engineers can face ethical dilemmas of all forms. In Engineering Ethics: Real-World Case Studies, Starrett, Lara, and Bertha provide in-depth analysis with extended discussions and study questions of case studies that are based on real work situations. Important concepts such as rights and obligations; conflict of interest; professionalism and mentoring; confidentiality; whistleblowing; bribery, fraud, and corruption; and ethical communication with the public in a social media world are discussed in practical and approachable terms. Organized by the canons of the ASCE Code of Ethics, this book is intended for practitioners, consultants, government engineers, engineering educators, and students in all engineering disciplines"--The publisher.
Introduction to ethics -- Hold safety paramount -- Service with competence -- Issue true statements -- Act as a faithful agent -- Reputation by merit -- Uphold professional honor -- Continue professional development -- Complex case studies -- Conclusions and resources.
Includes bibliographical references (pages131-135) and index.
Keywords: Engineering ethics -- Case studies